A Novel Low Voltage Low Power OTA Based on Level Shifter Current Mirror - Sokmen, Okkes Gokalp; Ercan, Hamdi; Tekin, Sezai Alper; Alci, Mustafa (Elektronika ir Elektrotechnika, 2015)
In this paper, a low voltage low power operational transconductance amplifier (OTA) structure is proposed. To achieve the low voltage low power operation, level shifter current mirrors are employed in the circuit structure. The proposed structure operates at ±0.5 V as supply voltages and dissipates power as 83 µW. Positive and negative slew rate of the circuit is 223 V/µs and 162 V/µs, respectively. Furthermore, the bandwidth of the circuit is about 80 MHz. The designed OTA is simulated with 0.18 µm TSMC CMOS technology parameters using SPICE. Simulation results have been justified the theoretical approach. DOI: http://dx.doi.org/10.5755/j01.eee.21.2.115011